Intellectual Change before the Enlightenment: Scotland, the Netherlands and the Reception of Cartesian Thought, 1650–1700. (April 2015) - Raffe, Alasdair
Abstract : This article argues that intellectual historians' fascination with a narrative of the emerging Scottish enlightenment has led to a neglect of ideas that did not shape enlightenment culture. As a contribution to a less teleological intellectual history of Scotland, the article examines the reception of the philosophy of René Descartes (1596–1650). Cartesian thought enjoyed a brief period of popularity from the 1670s to the 1690s but appeared outdated by the mid-eighteenth century. Debates about Cartesianism illustrate the ways in which late seventeenth-century Scottish intellectual life was conditioned by the rivalry between presbyterians and episcopalians, and by fears that new philosophy would undermine christianity. Moreover, the reception of Cartesian thought exemplifies intellectual connections between Scotland and the Netherlands. Not only did Descartes' philosophy win its first supporters in the United Provinces, but the Dutch Republic also provided the arguments employed by the main Scottish critics of Cartesianism. In this period the Netherlands was both a source of philosophical innovation and of conservative reaction to intellectual change.